Rancang Bangun Aplikasi Wifi-Call untuk Panggilan pada Local Area Network Berbasis Android (Studi Kasus Universitas Muhammadiyah Bengkulu) - Toyib, Rozali; Darnita, Yulia; Sugianto, Melani (Jurnal Media Infotama, 2018)
The Local Area Network network at Muhammadiyah University of Bengkulu is equipped with good facilities, but there is not yet a communication system that makes it easy for lecturers and staff to exchange information, especially in the Faculty of Engineering. To use telephone services certainly requires quite a lot of money and also requires the use of quite a lot of telephone sets, especially since postpaid telephone services must be paid for every month. When planning a VoIP network, you must have a server that functions as an IP PBX. In other conditions, such as at the Faculty of Engineering, Muhammadiyah University of Bengkulu, this tool will be useful for lecturers and staff as a long-distance communication tool by utilizing LAN or WIFI networks so that they can be connected to each other so that work processes are coordinated. started implementing wireless technology or what is usually called Wireless Fidelity (WiFi0). Mobile phones which were originally used as communication tools, now have more than their basic functions, various features have been embedded, such as image and video processing, document processing and so on. , this cannot be separated from the use of the Operating System on Android Mobile. The Android Operating System has the main goal of advancing innovation in mobile telephone devices so that users are able to explore capabilities and add more experience compared to other mobile platforms. From the results, testing the Wifi-Call Application for Calls on Local Area Network Based on Android, can be concluded as follows: The Wifi-Call application created can be used over a distance of less than 10M. The trial of 3 Smartphones was successful with different OS versions, it is possible that other brands of Smartphones can also be successful. Under the circumstances The connection is off and on. This application can still be run because this system only uses the network. The voice response produced by the system that the author created experienced a delay of more than 1 second. This Wifi-Call application has been successfully tested in two different locations, namely campus and 1 and 2 Muhammadiyah Bengkulu Universities.